2007
DOI: 10.1038/sj.ejcn.1602903
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropylmethylcellulose significantly lowers blood cholesterol in mildly hypercholesterolemic human subjects

Abstract: Objective: To determine the cholesterol-lowering efficacy of hydroxypropylmethylcellulose (HPMC) , and 12 and 15% at 15 g day À1 , respectively, over placebo. Adverse effects were minimal. Trial one: medium, high and ultra-high viscosity HPMC at 15 g day À1 for 1 week each; 1-week wash-out between treatments. Trial two: ultra-high viscosity HPMC at 5 or 15 g day À1 for 8 weeks. Conclusions: HPMC soluble fiber, especially high-viscosity grades, significantly lowers cholesterol at well-tolerated doses, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
1
28
1
1
Order By: Relevance
“…Although several previous trials have demonstrated the cholesterol-lowering efficacy of HPMC alone (Dressman et al, 1993;Maki et al, 1999Maki et al, , 2000Reppas et al, 2009), this study is the first to examine HPMC as an adjunct to statin therapy. On the basis of results from a meta-analysis of studies that provided 2-10 g per day of viscous fiber (Brown et al, 1999), mean reductions in LDL-C of 0.037-0.067 mmol/l have been observed per gram viscous fiber from oat products, psyllium, pectin and guar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several previous trials have demonstrated the cholesterol-lowering efficacy of HPMC alone (Dressman et al, 1993;Maki et al, 1999Maki et al, , 2000Reppas et al, 2009), this study is the first to examine HPMC as an adjunct to statin therapy. On the basis of results from a meta-analysis of studies that provided 2-10 g per day of viscous fiber (Brown et al, 1999), mean reductions in LDL-C of 0.037-0.067 mmol/l have been observed per gram viscous fiber from oat products, psyllium, pectin and guar.…”
Section: Discussionmentioning
confidence: 99%
“…When ingested, HPMC forms a viscous solution in the gastrointestinal tract, thereby acting as a physical barrier to the degradation of gastrointestinal contents, delaying the absorption of cholesterol, bile acids and glucose (Reppas et al, 1991(Reppas et al, , 1999Carr et al, 1996). HPMC has been shown to blunt postprandial glucose and insulin elevations (Reppas et al, 1993;Maki et al, 2007Maki et al, , 2008 and to reduce fasting TC and LDL-C concentrations (Dressman et al, 1993;Maki et al, 1999Maki et al, , 2000Reppas et al, 2009). In previous trials, our group has demonstrated that consumption of 5.0 g per day of high-viscosity HPMC with meals lowered LDL-C by 9-13% (Maki et al, 1999(Maki et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…2). On the contrary, unlike other polysaccharide-type modulators such as chitosan, b-glucans and hydroxypropylmethylcellulose, [32][33][34] the Triton WR1339-induced increase in TC concentration was not significantly affected by RGAP treatment, although there was an inhibitory tendency at higher doses (500, 1000 mg/kg) (Fig. 2).…”
Section: Resultsmentioning
confidence: 77%
“…Thirteen randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to fasting blood lipids (Bell et al, 1990;Ryle et al, 1990;Landin et al, 1992;Vido et al, 1993;Mee & Gee, 1997;Pasman et al, 1997b;Panlasigui et al, 2003;Marett & Slavin, 2004;Lehtimaki et al, 2005;Schwab et al, 2006;Garcia et al, 2006;Wood et al, 2007;Reppas et al, 2009) Two trials could not be included in meta-analysis (Vido et al, 1993;Pasman et al, 1997b), but demonstrated no significant effect of fibre isolates and gum supplements on fasting blood lipids. One trial only provided data for fasting triacylglycerol concentration (Landin et al, 1992).…”
Section: Mixed Isolated Fibre Interventionsmentioning
confidence: 99%